Attitudes towards and use of dental dams by final-year dental students in Chongqing, China: a cross-sectional study. Issue 7 (13th July 2022) - Jiang, Haofeng; Shen, Lu; Zhang, Yuhan; Yang, Jing
Abstract : Objectives: To investigate the current and intended future use of dental dams (DDs) and attitudes regarding DD use among final-year dental students at two levels (undergraduate and college) in dental schools in Chongqing, China. Design: A cross-sectional study based on a questionnaire was conducted from June to July 2021. Setting: Chongqing Medical University (CQMU, undergraduate level) and Chongqing Three Gorges Medical College (CQTGMC, junior college level). Participants: A total of 245 final-year dental students. Main outcome measures: An anonymous online questionnaire was distributed to dental students less than 1 month before graduation. Students were asked about the DD training they had received, their attitudes towards some aspects of DDs, their current DD use and their intended future DD use in adult or child patients and in various dental procedures. Results: A total of 238 valid questionnaires were returned (response rate=97.1%, CQMU=96.2%, n=76; CQTGMC=97.6%, n=162). A total of 47.5% of respondents used DDs on real patients during their internships (CQMU=59.2%, CQTGMC=42.0%, p<0.05). Whether in restorative procedures or endodontic treatment, the most common reason for not using DDs was a 'lack of knowledge and experience', followed by 'DDs could not be provided by internship institutions'. Although the advantages of DDs were recognised by most students from the two schools, 52.9% thought DDs were difficult to apply (CQMU=42.1%, CQTGMC=58.0%, p<0.05). A total of 92.1% of CQMU respondents and 95.1% of CQTGMC respondents expressed their willingness to use DDs after independent practice in the future. Conclusions: Although final-year students have a clear awareness of the advantages of DDs and are very enthusiastic about future DD use, the current DD utilisation rate is low. Education about DDs should be continuously improved in many aspects, and the advantages of using DDs in clinical dentistry should be further emphasised at dental schools.